Pasiones devoradoras y sentimientos trágicos. El tema del amor en algunas canciones rituales ganaderas de los Andes - Rivera, Juan J. (Revista de Antropología Social, 2008)
This article will examine a certain sentimental education. It will try to describe the emotional world of the people who participates in the cattle branding rituals of the Lima Highlands (Peru). This sentimental ethnography will be restricted to the corpus of songs recollected in a specific region -the Chancay valley peasant communities- by the author and an anthropologist who was there forty years ago. I will try to depict the kind of feelings that these songs express. I will not consider them as being part of a coherent ideology but rather as critical and also contradictory comments. These comments give us a modern Andean peasantry perspective about their ecology, their way of life and the recent modernization processes in the region. Their perspective in these ritual songs seems to be translated into the vocabulary of passions, particularly the unfortunate love. Actually, the cattle branding ritual in which the songs appear constitute a space in which cattle farmers must symbolically appropriate their animals and at the same time send them to death selling them to the slaughterhouses of the city.
Keywords: Andes; Cattle farming; Orality; Love; Anthropology of emotions